Usability and Display Evaluation of Job Vacancy Platform (Website X and Website Y) - Thalia Naziha; Gloria Elsa Ave C; Adinda Mutiara Santi (Agroindustrial Journal, 2022)
One of the impacts of the COVID-19 pandemic is the delay in face-to-face activities, one of which is the delay in holding job fair event. The reduction in the implementation of offline job fairs has encouraged job seekers to seek work through online media. Website X and Website Y are examples of websites used to find jobs online. With the current increase in find jobs through Website X and Website Y, the usability and display of their website need to be evaluated. Usability and display evaluation aims to identify usability problems and correct these problems, to increase the usability of a design. The objective of this study is to find out whether there is a significant difference of the time needed to find job vacancy between Website X and Website Y website, to find out whether there is a significant difference of the time needed to find job vacancy between male and female on both Website X and Website Y website, and to find out user perspective on both Website X and Website Y website related to system aspects, user aspects, and interaction aspects by using usability questionnaire. The advantage of this research is that it can help website developers by pointing out areas that require development or improvement. Other than that, this study might provide suggestions for job vacancy websites that are more user-friendly. Based on the results of the study it was found that Website X and Website Y had problems related to user perceptions of the safety of using the website, user comfort with using colors on the website, and the user's ability to remember menus and website appearance. The results also show that there is a significant difference between the time needed to carry out activities on Website X and Website Y.